Thermosuperrepellency of a hot substrate caused by vapour percolation - J. Benedikt Schmidt (Nature Portfolio, 2021)
Droplet impact on surfaces has wide applications regardless of the discipline area and several hypotheses have been put forward to explain the mechanism of film boiling. Here, the authors combine theory and experiment to investigate liquid drop impact off hot hydrophilic substrates, and explain the transition between deposition and rebound in terms of vapour percolation.